Job polarization in the United States in the 21st century studying shifts in employment structures using occupations and sectors - Rachel E. Dwyer (European Commission, Joint Research Centre (JRC), 2023)
Job polarization was first identified in the US in the 1990s, when employment growth concentrated in the highest and lowest wages jobs with much less growth in middle wage jobs. Research since then has identified continuing polarizing pressures in the US and Europe, but also evidence of job upgrading in some periods even in the US. Prior research on job polarization often focuses on the relationship between individual wage inequality and inequality between jobs defined as occupations. I argue for the value of a focus on the structure of job inequality as distinct from individual wage inequality and, furthermore, argue for the inclusion of sectoral divisions in a jobs-based approach. With that conceptual underpinning, I analyze CPS data and build on prior work to study the first two decades of the 2000s, up to the first pandemic year of 2020. I disaggregate job growth by sector, employment contract, and sociodemographic groups. I find that the pattern of job polarization shifted in the 2000s where economic recessions became increasingly crucial in shaping the evolution of job growth. I also find striking race/ethnic disparities in job growth that reinforce both the privileged position of white workers in the US labor market, but also challenges for white workers in middle-wage jobs. Black and Hispanic workers also face particularly significant obstacles in reaching the highest-wage jobs. I close with policy recommendations for supporting equitable job growth.
Keywords: 330; Employment growth; job quality; sectoral change; gender and work